Pengembangan Kurikulum Pendidikan Agama Islam dalam Pengarusutamaan Moderasi Beragama di Sekolah - Thohiri, M. Kholid; Sunarko, Dadang (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
In the strengthening the discourse on character education, religious moderation, as well as overcoming radicalism and terrorism with religious nuances. So the importance of developing the PAI curriculum is directed at the formation of students' moderate religious understanding. especially at the school level in Sendang sub-district, especially SMP Negeri 1 Sendang Tulungagung, which has a plurality of religions and very diverse cultures and societal traditions.The Purpose of this research is first, to find out the planning for developing the Islamic Religious Education Curriculum in mainstreaming religious moderation at SMP Negeri 01 Sendang. Secondly, to find out the implementation of the Islamic Religious Education Curriculum in mainstreaming religious moderation at SMP Negeri 01 Sendang. this research use desciptive qualitative approach. The results of the research explain firstly: Planning for the development of an Islamic religious education curriculum in mainstreaming religious moderation at SMP Negeri 1 Sendang in an integrated manner based on Islamic and national values and integrating mastery of material or theory, practice and habituation of morals through uswatun hasanah.Second, the implementation of PAI curriculum development in mainstreaming religious moderation at SMP Negeri 1 Sendang is education and teaching of religious moderation in the classroom and outside the classroom through local cultural extracurricular activities and the habituation of Islamic religion.